Titling of ancestral domain and its relationship with the formulation of ancestral domain sustainable development and protection plans the case of Happy Hallow ancestral domain in Baguio City - Reyes, Giovanni Soliman B. (School of Urban and Regional Planning, University of the Philippines Diliman, 2016)
In the Philippines, an Ancestral Domain Sustainable Development and Protection Plans (ADSDPP) is a fundamental expression of ownership rights of the Indigenous Cultural Communities/Indigenous Peoples (ICCs/IPs) over their ancestral domain. The National Commission on Indigenous Peoples (NCIP) is the primary government agency responsible for the effective development planning process for all ICCs?IPs. This study inquires how an ADSDPP could be sustainable as a protection plan when a CADT on which it is anchored on is infirm. Semi-structured individual interviews and Focus Group Discussions (FGDs) were conducted to elicit the history of ancestral domain claim, and to gather information on the experiences, observations and comments of community members. A number of official documents from the Office of the Executive Secretary (OES,NCIP,DENR among others, were obtained. The data collected contributed in identifying policy influences that helped shape the nature and character of NCIP and how this has affected the implementation of the Indigenous Peoples' Rights Act in terms of ancestral domain titling and formulation of the ADSDPPs.The study applied Rajesh Tandon's concept where he stated that realities on the ground do not necessarily match with the categorization that government represents the primacy of being the "first" sector, the corporations or business as the "second" sector and civil society as the "third" sector. The "first" sector purpose to determine the manner in which families, institutions, associations and communities are to be managed. This study ascertained that indigenous peoples possess the readiness and, are astute when engaging government and civil society pertaining to laws on indigenous peoples' rights to ancestral land domain. This readiness to meet situations is shaped by and, the outcome of Indigenous Peoples' history of land dispossession and marginalization. It is from such historical context that Happy Hallow's traditional Ibaloi leaders read these laws unabashedly of these laws and participation in workshops formed key inputs in the formulation of the government's Special Orders on ancestral land and domain claims. These Special Orders in turn formed important provisions in the Indigenous Peoples' Rights Act of 1997. Ironically, the IPRA law as implemented in the area where it all began, became a tool for unscrupulous survey proceedings resulting in the distortion of ancestral land and domain. The study recommends institutional reorganization of the NCIP, an amendment of the Happy Hallow CADT in order to reflect the community's traditional boundaries, metes and bounds and the reformulation of the ADSPP with the full participation of community members. It proposes mapping and resource inventory of the Happy Hallow ancestral domain to ensure that natural resource use and management are bounded by people's needs and aspiration. It utilizes planning as a community event. As such, planning serves as a venue and as a process whereby the community's general physical development will be interwoven with the social, political, cultural and bio-physical concerns of the people.